Scribal Corrections in Early Greek New Testament Manuscripts: The Fragments. - Cole, Zachary J.; Shandroski, Randall M. (TC: A Journal of Biblical Textual Criticism, 2023)
This study catalogs and categorizes the scribal corrections found in the earliest fragmentary Greek New Testament manuscripts (second-fourth/fifth centuries). Although corrections are normally identified and discussed by manuscript editors, this analysis gathers such evidence from a wide range of artifacts in order to observe relevant trends in scribal habits across the group as a whole. Corrections are identified in the earliest 114 fragmentary manuscripts of the New Testament, including papyri and parchment. These corrections are then categorized and discussed, with attention given to the copying process, text-critical evidence, and the identity of the correctors.